Molecular detection of Borrelia anserina in Argas persicus (Acari: Argasidae) ticks collected from Lorestan province, west of Iran - Asadollah Hosseini Chegeni; Zakkyeh Telmadarraiy; Majid Tavakoli; Faezeh Faghihi (Persian Journal of Acarology)
Borrelia anserina is the agent of avian borreliosis, an acute septicemic disease of a variety of avian species in tropical and warm temperate regions of the world. Avian borreliosis is one of the most widespread poultry diseases in Iran, and is of great economic importance. The present study was designed to detect B. anserina in Argas persicus ticks. Specimens were collected from the cracks of aviary in Lorestan province of Iran. Then the salivary glands, ovaries and uterus of ticks were dissected to detect B. anserina within the specific organ using molecular methods. DNA was extracted by Phenol-chloroform method and then a fragment of flagellin gene (flaB) of B. anserina was amplified by polymerase chain reaction. According to our results, the flaB target fragment was detected in Argas persicus ticks collected from Lorestan province. It seems that B. anserina is widely distributed in A. persicus vector ticks. Based on the result, B. anserina strain of Iran is similar to B. anserina flaB sequences reported from other parts the world.